Frequency stabilization of a laser system for Rydberg spectroscopy - Pham, Hoa (2016)
Our purpose in this final year project is to stabilize the 780 nm diode laser system . The method that is adopted in this project is to lock the frequency of the laser beam onto the resonant frequency of a stable Fabry-Perot cavity. The laser and the resonator are included in a feedback loop. This feedback loop continuosly calculate the difference between the frequency of the laser and the resonant frequency of the resonator to generate the error signal. This error signal is then fedback into the laser in order to counteract any shift in the frequency of the laser.